The Histopathological Features of Endometrial Tissue Specimens in Women With Peri and Post-Menopausal Bleeding in Hillah City, Iraq - Kadhim , Farah Abdulhussein; Almanadi , Feed Tawfeeq Abdulameer (Iraqi Journal of Science, 2026)
Abnormal bleeding from the uterus is one of the most common concerns in gynecological clinics. The main purpose of this research was to investigate the histopathological characteristics of endometrial tissue samples in women suffering from peri-menopause and post-menopausal bleeding in Hillah, Iraq. This is a cross-sectional descriptive-analytical study on 110 patients with abnormal uterine bleeding who visited a private laboratory in Hillah, Iraq, from January 2022 to December 2023 and were hospitalized and underwent diagnostic curettage (C and D), total abdominal hysterectomy (TAH), bilateral salpingo-oophorectomy (BSO) or TAH and BSO were placed. The results showed that the most common type of abnormal uterine bleeding among the women studied was Menorrhagia, followed by Post-menopausal bleeding. Also, the results of this study showed that the relationship between the bleeding pattern and the histopathological pattern is significant with age ranges, but there was no significant relationship between the cause of bleeding and age range. Due to the prevalence and importance of this disease, many similar studies have been conducted all over the world, but since this is an epidemiological issue, the results may not be the same in different populations and races. The results of the study showed that the evaluation of histopathology is valuable and provides more accurate information about the cause of abnormal uterine bleeding, such as polyps and hyperplasia. This evaluation will help early detection of endometrial malignancy, which has a worse prognosis, to be identified earlier and to receive appropriate treatment as soon as possible.